Subarachnoid Hemorrhage Induces Dynamic Immune Cell Reactions in the Choroid Plexus - Solár, Peter; Klusáková, Ilona; Jančálek, Radim; Dubový, Petr; Joukal, Marek (Frontiers in Cellular Neuroscience, 2020)
Subarachnoid hemorrhage (SAH) is a specific form of hemorrhagic stroke that frequently causes intracranial hypertension. The choroid plexus (CP) of the brain ventricles is responsible for producing cerebrospinal fluid and forms the blood – cerebrospinal fluid barrier. The aim of the current study was to determine whether SAH induces an immune cell reaction in the CP. and whether the resulting increase in intracranial pressure (ICP) itself can lead to cellular changes in the CP. SAH was induced by injecting non-heparinized autologous blood to the cisterna magna. Artificial cerebrospinal fluid (ACSF) instead of blood was used to assess influence of increased ICP alone. SAH and ACSF animals were left to survive for 1, 3 and 7 days. SAH induced significantly increased numbers of M1 (ED1+, CCR7+) and M2 (ED2+, CD206+) macrophages as well as MHC-II+ antigen presenting cells (APC) compared to naïve and control ACSF animals. Increased numbers of ED1+ macrophages and APC were found in the CP only 3 and 7 days after ACSF injection, while ED2+ macrophage number did not increase. CD3+ T cells were not found in any of the animals. Following SAH, proliferation activity in the CP gradually increased over time while ACSF application induced higher cellular proliferation only 1 and 3 days after injection. Our results show that SAH induces an immune reaction in the CP resulting in an increase in the number of several macrophage types in the epiplexus position. Moreover, we also found that increased ICP due to ACSF application induced both an immune reaction and increased proliferation of epiplexus cells in the CP. These findings indicate that increased ICP, and not just blood, contributes to cellular changes in the CP following SAH.